2010
DOI: 10.1007/s00436-010-1797-y
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory evaluation of traditionally used plant-based insect repellent against the malaria vector Anopheles arabiensis Patton (Diptera: Culicidae)

Abstract: A laboratory study was carried out to evaluate the repellent efficacy of a methanol-leaf extract of Ethiopian traditionally used insect repellent plant viz., Lomi sar [vernacular name (local native language, Amharic); Cymbopogon citratus (DC) Stapf. (Poaceae)] against Anopheles arabiensis at four different concentrations viz., 1.0, 1.5, 2.0, and 2.5 mg/cm(2). The percentage protection in relation to the dose method was performed. C. citratus extract has shown various degrees of repellency impact against A. ara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…In most household studied, the children's (aged between 1 and 3 years) were given priority in using mosquito nets because of the fact that the disease symptoms of the kids are difficult to understand and follow up medical treatment. Indigenous repelling methods adapted by the local community include smoke production by burning the plant parts, growing of the plant species (Azadirachta indica, Annona squamosa, Artemisia vulgaris, Cymbopogon citratus, Lantana camara, Ocimum sanctum, and Vitex peduncularis) nearby residential area or settlement area, and polishing of house floor with leaf plant extracts obtained from the species of Azadirachta (Sharma et al, 1993a,b), Artemisia (Yit et al, 1985), Lantana (Dua et al, 1996), Ocimum , and Cymbopogon (Karunamoorthi et al, 2010) was routinely done to drive away mosquitoes and other insect's flies and they are commonly used as insect repellent against the mosquito vectors (see Table 2). …”
Section: Discussionmentioning
confidence: 99%
“…In most household studied, the children's (aged between 1 and 3 years) were given priority in using mosquito nets because of the fact that the disease symptoms of the kids are difficult to understand and follow up medical treatment. Indigenous repelling methods adapted by the local community include smoke production by burning the plant parts, growing of the plant species (Azadirachta indica, Annona squamosa, Artemisia vulgaris, Cymbopogon citratus, Lantana camara, Ocimum sanctum, and Vitex peduncularis) nearby residential area or settlement area, and polishing of house floor with leaf plant extracts obtained from the species of Azadirachta (Sharma et al, 1993a,b), Artemisia (Yit et al, 1985), Lantana (Dua et al, 1996), Ocimum , and Cymbopogon (Karunamoorthi et al, 2010) was routinely done to drive away mosquitoes and other insect's flies and they are commonly used as insect repellent against the mosquito vectors (see Table 2). …”
Section: Discussionmentioning
confidence: 99%
“…Major victims for these malicious killers are the poorest resourceconstrained countries like Ethiopia (Karunamoorthi et al, 2010b). As a result, at the moment, there is growing acceptance and keen interest towards traditional medicines observed worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…The LC 50 values of chloroform extract of Nyctanthes arbor-tristis leaves were 303.2, 518.2, and 420.2 ppm against A. aegypti, A. stephensi, and C. quinquefasciatus, respectively. Karunamoorthi et al (2010) reported that the percentage protection in relation to the dose method was performed. C. citratus extract has shown various degrees of repellency impact against Anopheles arabiensis.…”
Section: Discussionmentioning
confidence: 99%